Salt of the River, Salt of the Earth. Politics, Science and Ecological Diplomacy in the Mexicali Valley (1961-1965) - Ward, Evan (Frontera Norte, 2017)
This article examines the salinity crisis in Mexicali Valley. National and state officials from both countries saw Mexicali Valley as a ground where their theories on the causation of the crisis would be vindicated by scientific testing of water and land conditions there. Those that viewed Mexicali Valley as an international political landscape did not live there, but recognized the importance of the region in resolving the crisis. Those who lived in Mexicali Valley viewed their home as a local political landscape. For them the salinity crisis was not an abstract issue that could be reduced to statistics or policy positions, but instead represented a profound ecological transformation that affected the taste of drinking water, the fertility of land, and the bounty of the harvest The concerns of local political organizers, such as Alfonzo Garzón, founder of the State Agrarian league of Baja California (LAE), often worked at cross-purposes to those of national officials. In fact, one of the turning points in the salinity crisis occurred around 1964, when the diplomacy-driven perspective subsumed the agenda of many local officials in Mexicali Valley. RESUMEN En este artículo se examina la crisis de salinidad en el Valle de Mexicali. Las preguntas que hicieron los creadores de políticas y los científicos de cada nación durante la crisis estaban, por lo general, prejuiciadas por sus percepciones de cómo y por qué surgió la crisis. Aquellos que veían al Valle de Mexicali como un terreno de política internacional no vivían ahí, pero reconocían la importancia de la región en la solución de la crisis, y aquellos que vivían en el Valle de Mexicali veían su hogar como un terreno de política local; para ellos la crisis de salinidad no era un problema abstracto que podía ser reducido a estadísticas o posturas políticas: representaba una profunda transformación ecológica que afectaba el sabor del agua potable, la fertilidad de la tierra y la generosidad de la cosecha. Las preocupaciones de organizadores políticos locales, tales como Alfonso Garzón, fundador de la liga Agraria Estatal (LAE), con frecuencia trabajaban con propósitos contrarios a aquellos de los funcionaros federales. De hecho, uno de los momentos cruciales en la crisis de salinidad ocurrió por 1964, cuando la perspectiva motivada por la diplomacia se incluyó en la agenda de funcionarios locales del Valle de Mexicali.